Between the Comneni and the Angeli: images of «greatness» before the «catastrophe» (Bisanzio e l'Occidente, 2018)
The article aims to outline a framework of the Byzantine imperial art during the last troubled years of the 12th century, which led to the Latin capture of Constantinople in 1204. Although few case studies from different sectors survive, Nicetas Choniates’ «Chronike Diegesis» offers a vivid account of the imperial patronage of his time, concerning also the reign of Andronicus I, the last Comnenian ruler, and the period of the two Angelids, Isaac II and Alexius III. The indications provided by Nicetas and other coeval literary sources attest the flourishing of all sectors of production, in connection with both monumental and luxury arts. The restoration of churches, endowed with paintings and precious objects, the execution of public works and the interest in secular cycles too show the use of imperial patronage and imagery as means to celebrate political and military power in light of a period of crisis. Coins and lead seals offer a material counterpart to the lost monuments and representations attested, on a large scale, by Byzantine authors and constitute the most suitable vehicle for ideological messages. This need clearly appears in the case of Andronicus I, who usurped the throne at the expense of the young nephew Alexius II, as well as in the case of Isaac II, who tried to establish a new dynasty exalting the Angelid name and, in a different way, in the instance of Alexius III, who revived the family link to the Comnenian clan. The capture of Constantinople by the Crusaders marked the end of the middle-Byzantine imperial patronage but, paradoxically, beside the destructions, the extensive plunder of artworks, many of which entered Western collections, helped to preserve the legacy of the Byzantine civilisation.
Keywords: History of Byzantine art